The Mechanisms of Influencing Consumer Perceived Value in New-Style Tea Beverages from a Brand Alliance Perspective - Wang, Li; Hye, A. K. Mahbubul (Journal of Dhamma for Life, 2026)
Brand co-branding has become an increasingly important marketing strategy in the fast-moving consumer goods (FMCG) sector, particularly in experiential product categories such as new-style tea beverages. Despite its widespread adoption, limited research has systematically examined how multiple dimensions of consumer perceived value contribute to overall value perceptions in co-branded FMCG products. Therefore, this study aimed to (1) describe the demographic characteristics of consumers and examine differences in perceived value across demographic groups, (2) investigate the effects of functional, emotional, and social value on overall consumer perceived value, and (3) examine the value formation mechanism underlying these three value dimensions in co-branded new-style tea beverages, with particular attention to their antecedent factors. A quantitative research design was employed using a structured questionnaire administered to 502 consumers who had prior experience purchasing co-branded new-style tea beverages. The questionnaire served as the primary research instrument. Data were analyzed using descriptive statistics to summarize demographic characteristics, confirmatory factor analysis (CFA) to validate the measurement model, and structural equation modeling (SEM) to test the hypothesized relationships among constructs. The findings revealed that functional value, emotional value, and social value all exert significant positive effects on consumer perceived value. Functional value emerged as the strongest determinant, serving as the primary basis for consumer evaluation, while emotional and social value provided complementary contributions that enhanced overall value perceptions. These findings enrich the literature on co-branding and consumption values by clarifying the distinct roles of multiple value dimensions in FMCG brand alliances and provide practical guidance for developing effective co-branding strategies that integrate functional quality, emotional engagement, and social appeal in experiential consumption markets.